Pengembangan TPS Kelurahan Bringin Berbasis 3R Kecamatan Sambikerep Kota Surabaya - Mohamad Mirwan; Dian Retno Hapsari (Prosiding ESEC, 2022)
Waste management in TPS Bringin Village which serves 5483 people is not in good operation. One approach that can be dealing the problem to reduce waste is the 3R method of waste management. The calculation method used in this planning refers to SNI 19-3964-1994. Based on the waste sampling that has been carried out, the volume of waste generated in Bringin Village reached 2,7 liters/people/day. This plan projects the age for TPS 3R is next 10 years, so the volume of waste generation in 2032 is 16,22 m3/day and waste composition was obtained in Bringin Village by organic waste 63,08% and inorganic waste 36,94%. The waste management and producing plan in TPS 3R Bringin Village is organic waste processed into aerobic composting with open bin method, while plastic waste is processed into plastic pellets, and inorganic waste is recovered. The amount of waste generation at TPS-3R Bringin Village is 2094,31 kg/day meanwhile, the residue transport to TPA Benowo is 1036,64 kg/day. There are 6 areas namely dropping area, waste sortir area, composting area, plastic waste management area, inorganic waste management area and residue area, and for the residue directly transported into TPA Benowo. The land required area for TPS 3R Bringin Village is 769,41 m2 and budget plan for this construction of TPS 3R is Rp 1.446.962.000,00.